2022
DOI: 10.1002/jdd.12915
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality approach for orthodontic education at School of Stomatology, Jinan University

Abstract: Objectives:The development of virtual reality (VR) has exerted an enormous impact on higher education. However, the VR application in dental education is still at an early stage in China. This study explored the usability of a VR application in training the practical skills of dental students. Methods: We first utilized the "system usability scale" (SUS) to verify the validity of the VR application in this study. Next, the VR training on orthodontic bracket bonding was experienced by the participants. The subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
(39 reference statements)
1
4
0
Order By: Relevance
“…Our study indicated that CBL- method effectively enhanced students’ individual and team operation abilities, which have also been supported by previous studies [ 7 , 8 , 33 ]. Shih et al.…”
Section: Discussionsupporting
confidence: 91%
“…Our study indicated that CBL- method effectively enhanced students’ individual and team operation abilities, which have also been supported by previous studies [ 7 , 8 , 33 ]. Shih et al.…”
Section: Discussionsupporting
confidence: 91%
“…Some students seemed not to strongly agree that VR could be more efficient and provide sufficient learning. Their acceptance toward the VR training on dental implantation was not so high as the attitudes toward another training module we did almost the same period, the VR training module of orthodontic bracket bonding ( Huang et al, 2022 ). We analyzed the reason might be the different natures of these two modules.…”
Section: Discussionmentioning
confidence: 86%
“…The VR system was set up as previously described ( Huang et al, 2022 ). Specifically, the VR system used in this study (Shanghai VR-Sens Intelligent Technology Co. Ltd., Shanghai, China) consisted of a VR interface, a VR headset, two controllers, and two cameras ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The authors validated the VR application's effectiveness using the System Usability Scale (SUS) and analyzed the data collected on participants' perceptions. Overall, the VR training in dental education yielded positive outcomes, with participants finding the learning experience enjoyable and repeatable without extra costs [78]. A randomized trial was recently conducted at Kermanshah University of Medical Sciences, Iran.…”
Section: Dynamic and Diverse Environmentmentioning
confidence: 99%